Del derecho al ambiente hacia los derechos del ambiente: implicancias de una nueva subjetividad ambiental en el Sistema Interamericano de Derechos Humanos - Zorzin, Natalia Danae (2021)
This work obtained first place in the XVIII "Dr. Ignacio Winizky" essay contest on environmental law. -- The human right to a healthy environment was built around a traditional paradigm that ignores the development of Nature as a subject of rights, which is characteristic of the Indigenous peoples and tribal communities? cultures around the world, but especially in Latin America. This paper aims to briefly demonstrate that the human rights protection bodies at the American level have at their disposal several tools to develop a truly pluricultural interpretation in environmental matters, as well as the power to recognize the ownership of the right to a healthy environment to Nature itself, as a subject. To this end, I will analyze some of the greening practices of international law, as well as the doctrine of "good living", typical of Latin American indigenous communities. In addition, I will address different philosophical and juridical foundations to justify the viability of the hypothesis. Finally, I will conclude that it is indeed possible for the Inter-American human rights system to set aside the anthropocentric approach to the right to a healthy environment and adopt a "biocentric" conception. In this respect, human beings would abandon our character as the sole subjects of this right, in favor of Nature itself, as an entity of which we only form a small part